Routing protocol design for secure WSN: Review and open research issues - Md Zin, Shazana; Anuar, Nor Badrul; Mat Kiah, Miss Laiha; Pathan, Al-Sakib Khan (Elsevier, USA, 2014)
Wireless sensor networks (WSNs) have gained a substantial attention in wireless research community as these networks are envisioned to support a large number of practical applications. Due to salient features of sensor networks, the security design for WSN is significantly challenging. Despite a good number of available surveys on this particular topic, we feel that there is a gap in the existing literature in terms of timeliness, emphasis, and comprehensiveness. This paper reviews the state-of-the-art for secure WSN routing protocols that illustrates the issues and challenges in the context design matters. Further, we propose the schematic taxonomy of key design issues for WSN routing protocols. We also define design factors categorization relevant to secure routing: basic, essential, and optional. The similarities and differences of secure routing approaches are summarized on the basis of key design attributes, security objectives, and attacks prevention. Finally, we outline possible future research trends on secure routing design in WSN.